A Mistagogia de Cirilo de Jerusalém como referencial no processo de iniciação a vida cristã pós Vaticano II. - Oliveira, José Janédson de (2021)
This study takes part of the research that discusses the initiation bibliographic to the Christian life, including the 3rd and 4th centuries, a period in which it was institutionalized by the Holy Fathers and the decades after Vatican II, marked by profound changes in the Church. Thus, the objective for a bibliographic study is to analyze Cyril of Jerusalem's mystagogical catechesis that present the process of initiation to Christian life as a mystagogical and theological catechumenal path, in the perspective of relating them to the Church's evangelizing practice today, marked by new configurations in subjectivity human. The results point to Cyril of Jerusalem's mystagogical catechesis as references for the catechetical process of the post-conciliar Church, which takes up the catechumenate as an overcoming of the existing practice of Christian initiation through a mystagogical catechumenal formation in light of the sociocultural contexts that involve it and official documents instituted by the church. It is also clear that the converging points between the two ecclesiological contexts, the third and fourth centuries and the years after Vatican II, which despite being historically separated, are united by the same ecclesial, mystagogical and ecclesiological perspective.